Therapeutic Target and Cell-signal Communication of Chlorpromazine and Promethazine in Attenuating Blood–Brain Barrier Disruption after Ischemic Stroke - Fengwu Li; Xiaokun Geng; James Yip; Yuchuan Ding (Cell Transplantation, 2019)
Ischemic stroke destroys blood–brain barrier (BBB) integrity. There are currently no effective treatments available in the clinical setting. Post-ischemia treatment with phenothiazine drugs [combined chlorpromazine and promethazine (C+P)] has been shown to be neuroprotective in stroke. The present study determined the effect of C+P in BBB integrity. Sprague-Dawley rats were divided into the following groups ( n =8 each): (1) stroke, (2) stroke treated by C+P with temperature control, and (3) stroke treated by C+P without temperature control. Infarct volume and neurological deficits were measured to assess the neuroprotective effect of C+P. BBB permeability was determined by brain edema and Evans blue leakage. Expression of BBB integral molecules, including proteins of aquaporin-4 and -9 (AQP-4, AQP-9), matrix metalloproteinase-2 and -9 (MMP-2, MMP-9), zonula occludens-1 (ZO-1), claudin-1/5, occludin, and laminin were determined by Western blot. Stroke caused brain infarction and neurological deficits, as well as BBB damage, which were all attenuated by C+P through drug-induced hypothermia. When the reduced temperature was controlled to physiological levels, C+P still conferred neuroprotection, suggesting a therapeutic effect independent of hypothermia. Furthermore, C+P significantly attenuated the increase in AQP-4, AQP-9, MMP-2, and MMP-9 levels after stroke, and reversed the decrease in tight junction protein (ZO-1, claudin-1/5, occludin) and basal laminar protein (laminin) levels. This study clearly indicates a beneficial effect of C+P on BBB integrity after stroke, which may be independent of drug-induced hypothermia. These findings further prove the clinical target and cell-signal communication of C+P treatment, which may direct us closer toward the development of an efficacious neuroprotective therapy.